The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.20452/pamw.15849
|View full text |Cite
|
Sign up to set email alerts
|

Link between cardiovascular disease and the risk of falling: A comprehensive review of the evidence

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License (CC BY-NC-SA 4.0), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 89 publications
0
3
0
6
Order By: Relevance
“…Chen and colleagues observed that around 24% of SARS-CoV-2-infected patients present to the hospital with syncope, pre-syncope, and/or an associated fall [ 6 ], a finding which may in part be explained by cardiac rhythm disturbances in COVID-19 disease patients. Extensive research over the past decade has shown that arrhythmias are an important cause of cerebral hypoperfusion, syncope, and subsequent falls [ 19 21 ]. A systematic review and meta-analysis by Malik and colleagues on a total of 43 213 older adults found that atrial fibrillation was independently associated with syncope (odds ratio [OR], 1.19) and falls (OR, 1.88) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen and colleagues observed that around 24% of SARS-CoV-2-infected patients present to the hospital with syncope, pre-syncope, and/or an associated fall [ 6 ], a finding which may in part be explained by cardiac rhythm disturbances in COVID-19 disease patients. Extensive research over the past decade has shown that arrhythmias are an important cause of cerebral hypoperfusion, syncope, and subsequent falls [ 19 21 ]. A systematic review and meta-analysis by Malik and colleagues on a total of 43 213 older adults found that atrial fibrillation was independently associated with syncope (odds ratio [OR], 1.19) and falls (OR, 1.88) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although fall prevention strategies may benefit from incorporating rhythm management and anticoagulation in susceptible patients, these interventions may equally be detrimental in this patient population. Antiarrhythmics are arrhythmogenic and have been associated with both syncope and traumatic falls [ 29 ], while anticoagulants can increase a patient’s bleeding risk if a fall does occur [ 19 , 30 ]. The evidence is mixed, however, and this risk may not be significant enough to outweigh the benefits of anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of other risk factors for falls should thus be carefully explored and addressed where possible. Partly because of possible fluctuations in blood pressure and partly because of the mechanism of drug action, cardiovascular diseases increase not only the risk but also the severity of falls [11,19,20]. The risk of falls rises by 60% when using antiarrhythmic calcium channel blockers; by 20% when taking drugs containing digoxin; and by 10% when taking diuretics [15,21].…”
Section: Chronic Diseasesmentioning
confidence: 99%
“…Одна из самых серьезных травм у пациентов старческого возраста -перелом проксимального отдела бедра, в большинстве случаев обусловлена именно падением. Каждый год происходит 646 000 смертельных падений в мире [18].…”
unclassified
“…Вероятность падений увеличивается с возрастом, что объяснимо прогрессированием старческой астении и развитием саркопении. Возраст от 65 до 74 лет связан с 31 % риском падения, который увеличивается до 37 % в возрастной группе 80+ лет [18]. Женщины падают чаще мужчин, но наиболее наглядно это различие проявляется в более старшей возрастной группе [2,8].…”
unclassified